Pulmonary Outcomes in Survivors of Childhood Central Nervous System Malignancies: A Report from the Childhood Cancer Survivor Study - Huang, Tseng Tien (2013)
BACKGROUND: Adult survivors of childhood Central Nervous System (CNS) tumors may be at risk for pulmonary dysfunction. This study enumerates the incidence of pulmonary dysfunction and explores associations between craniospinal irradiation (CSI) and pulmonary dysfunction among survivors of childhood CNS tumors. METHODS: Participants included Childhood Cancer Survivor Study (CCSS) cohort members treated for CNS malignancies when < age 21, who survived five+ years, and sibling comparisons. Medical records were abstracted and participants completed questionnaires that asked about the nature and timing of pulmonary dysfunction. Incidence rates were calculated, and Poisson regression, adjusted for chemotherapy exposures, was used to evaluate associations between CSI and pulmonary dysfunction. RESULTS: Survivor participants (N=1,653) were 54.7% male, median age at diagnosis 7.6 (range 0–21), and median time from cohort entry 18.5 (range 3.3–33.9) years. The incidence of pulmonary dysfunction (per 1,000 person years) was 9.1 (95% CI 7.8–10.6) for emphysema/obliterative bronchiolitis and >3.0 for asthma, chronic cough and need for extra oxygen. Rates of fibrosis (RR 2.0, 95% CI 1.0–3.9), chest wall abnormalities (RR 19.0, 95% CI 4.2–85.7), chronic cough (RR 1.6, 95% CI 1.2–2.1) and need for supplemental oxygen (RR 2.5, 95% CI 1.9–3.3) were higher among survivors than among siblings. Survivors treated with CSI were 10.4 (95% CI 7.6–14.4) times more likely than those not exposed to report chest wall deformity. CONCLUSION: Adult survivors of CNS malignancy have high rates of pulmonary dysfunction 5+ years after diagnosis. Survivors treated with CSI should be monitored for pulmonary disease to permit early interventions.